The communications consultant's foundation leveraging public relations expertise for personal and client success - Darnell, Roger (London : Routledge, 2021)
For all professionals and students who want to improve their prospects in business, this book prepares and positions them to build dream careers, giving them the education and guidance required to develop vital soft skills, and work remotely and independently. After establishing a foundation for solid professional communications on a personal level, it quickly opens doors to business insights and opportunities that are exciting, inspiring, and highly sustainable. Immersing readers into the key realms of business success and exploring the full spectrum of essential communications practices, they gain knowledge and trade skills of immense value, including: The basics of positive, proactive, strategic communications for individuals and organizations What it means to be a PR expert in the creative industry and to do great work An introduction to essential business imperatives, with high-level instruction on creativity, strategy, leadership, management, marketing, and much more Customer service and all it entails Extensive exploration of the PR toolset and its application in real-world marketing scenarios This book brings home all instruction with sophisticated questions and challenges, ensuring readers have every opportunity to comprehend and grow, step by step.
Preface & Foreword; Part I Foundations; 1 Reputation Management and Ethics; 2 Creativity; 3 Strategy; 4 Personal Brands and Branding; Part II The Arena; 5 Leadership and Management; 6 Objectives; 7 Business Brands and Branding; 8 Business Development; 9 Customer Service; 10 Integrated Marketing in Action; 11 Cash Flow and Project Flow; Part III Communications Consulting; 12 The Communications Consultant in Practice; 13 Consistencies and Variations by Client Size; 14 Media and its Usage; 15 My Version and Your Version; 16 Is Consulting Right for You?
OCLC-licensed vendor bibliographic record.
Keywords: Public relations consultants -- Handbooks, manuals, etc; Public relations -- Vocational guidance; BUSINESS & ECONOMICS / Consulting; BUSINESS & ECONOMICS / Public Relations; BUSINESS & ECONOMICS / Industries / Media & Communications Industries